2013
DOI: 10.30638/eemj.2013.142
|View full text |Cite
|
Sign up to set email alerts
|

Application of Windings Shifting for the Optimization of Planar Structures

Abstract: The use of planar electromagnetic technology led to the improvement of high frequency characteristics of the structures and the decrease of their size and profile, which made them easier to integrate in different devices. In order to improve these planar structures, it is known that the parasitic capacitance (EPC) must be decreased. Another method to achieve a better functionality is to increase or decrease the high frequency losses, according to their use. Because the previous studies were made on an EMI filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It was concluded that the thickness of the dielectric influences the losses in the conductors. [9] The increase of its thickness not only decreases the losses, as it can be observed in the graph from Fig. 7, but also decreases the value of parasitic capacitances, as it was stated in previous research [5], which will lead to a better functionality of the device.…”
Section: B Influence Of the Dielectric Thickness On The Conductor Lomentioning
confidence: 63%
See 1 more Smart Citation
“…It was concluded that the thickness of the dielectric influences the losses in the conductors. [9] The increase of its thickness not only decreases the losses, as it can be observed in the graph from Fig. 7, but also decreases the value of parasitic capacitances, as it was stated in previous research [5], which will lead to a better functionality of the device.…”
Section: B Influence Of the Dielectric Thickness On The Conductor Lomentioning
confidence: 63%
“…(The glass used in laminates has a relative dielectric constant of 6.0.) [9] The woven glass reinforced materials have relative permittivities between 3.9 and 4.4, while for the non-woven materials the values are higher. The studied materials along with their characteristics are presented in Table 1.…”
Section: Influence Of Different Types Of Dielectrics On the Lossesmentioning
confidence: 97%
“…where the vector dl represents the differential element of the coil, the vector r is the distance from the coil element to the field point, and N is the number of turns of the coil. For coils of non-traditional shapes (Păcurar et al, 2013;Hebedean et al, 2013), one can compute A using an approximation method in which the contour of the coil is first divided into a variable number of equal segments, and the magnetic vector potential in the calculus point is obtained by adding the contribution of each segment to the final value.…”
Section: Main Section Mechanism Of Magnetic Stimulationmentioning
confidence: 99%